Hydrodynamics Simulation of Different Impeller Geometries Applied to Non-Newtonian Fluids in A Stirred Tank Reactor (2020)
In the present study bubble breakup and coalescence phenomena applied to non-newtonian fluids were simulated in order to characterize gas-liquid mass transfer in a 10 L bioreactor equipped with different impeller configurations. The mass transfer coefficient was estimated based on hydrodynamics simulation. Four geometries are proposed for analyzing flow pattern effect on gas liquid mass-transfer: Anchor Impeller (Radial Flow Pattern), Helical Impeller (axial upwards pumping), Interference Turbine (axial upwards and downwards pumping) and High Efficiency Turbine (axial downwards pumping). It was found that radial velocity flow patterns maximize as a consequence of its great capacity to break bubbles in Non-Newtonian fluids. The latter is confirmed by the highest values simulated using the Anchor Impeller. Also, it was found that pumping flow direction influences air dispersion: axial downwards pumping of High Efficiency Turbine generates better results in comparison to axial downwards pumping geometries (Helical Impeller). Motivated by results found on this work, the main criteria to design a device for improving of mass transfer in nonNewtonian applications are: (a) generating of radial, axial pumping down and shear velocities; (b) generating of small bubbles, and (c) generating of wall shear stress, lower than critical values reported according to references.